Governança corporativa e seus impactos na estrutura organizacional : o caso da SABESP - Bezerra, Angela Maria Domingues Biancolin (2007)
A lot of studies have tried to appraise the corporate governance by the financial results from the matching of implemented practices with so many performance indicators. The highest corporate governance purpose is really related to the amount of the company s maximize in stakeholders benefits, however its effectiveness must be observed by another angle besides the finances of short and long terms. To adopt the governance practices recognized by the market facilitates the access to the capital with low cost, however the demand whose the submited organization can have no planned effects. This study analyses the impacts created in an organization structure as a results of the corporate governance through case study research realized at Sabesp, one of the first companies listed in the Novo Mercado at the Stock Exchange of São Paulo Bovespa. The results showed that when recomendations and law obligations are taken over, hardened after the financial scandals which envolved big corporations as Enron, Sabesp passed by many important changes in its structure above all in is jobs process. It was also concluded that the organization can make from the itself an opportunity to introduce improvements continually. What makes it more flexible, but there s the risk of making it more bureaucratic if the potential of value improvement owned by the governance isn t realized.